Pengembangan Media Bata untuk Pembelajaran Tenses pada Jenjang Pendidikan Dasar - Novanita Whindi Arini (Jurnal Inovasi Pendidikan Dasar, 2016)
This developmental research tried to develop instruction media for student of elementary education to learn tenses. This research applied 4-D developmental model (four D models) from Thiagarajan (1974) with the research subject were the 5th grade students of the Baureno I State Elementary School. This model followed four phases: defining, designing, development, and dissemination. But due to the limitation of time, the 4-D model adopted in this research was only to development phases. The results of the data analysis to the product quality indicated that the Word Cube media developed have been suitable and qualified to use as observing tenses media of elementary education with 94%. The result of media implementation also indicated that there were increasing in student understanding of the tenses from 62.02% become 93.10%. This research was also successful to develop Word Cube media to observe tenses for elementary education in the form of (1) word cube, (2) base of cube, (3) instruction, and (4) the package. Generally, the conclusion of the research was one of the reasons that increase the student understands of tenses was Word Cube